Morphological and morphometrical assessment of spermathecae of Aedes aegypti females - Pascini, Tales Vicari; Ramalho-Ortigão, Marcelo; Martins, Gustavo Ferreira (My University, 2012)
The vectorial capacity of Aedes aegypti is directly influenced by its high reproductive output. Nevertheless, females are restricted to a single mating event, sufficient to acquire enough sperm to fertilize a lifetime supply of eggs. How Ae. aegypti is able to maintain viable spermatozoa remains a mystery. Male spermatozoa are stored within either of two spermathecae that in Ae. aegypti consist of one large and two smaller organs each. In addition, each organ is divided into reservoir, duct and glandular portions. Many aspects of the morphology of the spermatheca in virgin and inseminated Ae. aegypti were investigated here using a combination of light, confocal, electron and scanning microscopes, as well as histochemistry. The abundance of mitochondria and microvilli in spermathecal gland cells is suggestive of a secretory role and results obtained from periodic acid Schiff assays of cell apexes and lumens indicate that gland cells produce and secrete neutral polysaccharides probably related to maintenance of spermatozoa. These new data contribute to our understanding of gamete maintenance in the spermathecae of Ae. aegypti and to an improved general understanding of mosquito reproductive biology.
Citation: Pascini, Tales Vicari, Marcelo Ramalho-Ortigão, and Gustavo Ferreira Martins. (2012). Morphological and Morphometrical Assessment of Spermathecae of Aedes Aegypti Females. Memórias Do Instituto Oswaldo Cruz 107 (6): 705–12. https://doi.org/10.1590/S0074-02762012000600001.
Keywords: Mosquito reproductive system; Scanning electron microscopy; Transmission electron microscopy; Confocal microscopy; Histochemistry